2017
DOI: 10.1159/000480695
|View full text |Cite
|
Sign up to set email alerts
|

The Cerebellar-Cerebral Microstructure Is Disrupted at Multiple Sites in Very Preterm Infants with Cerebellar Haemorrhage

Abstract: Background: Recent advances in magnetic resonance imaging (MRI) techniques have prompted reconsideration of the anatomical correlates of adverse outcomes in preterm infants. The importance of the contribution made by the cerebellum is now increasingly appreciated. The effect of cerebellar haemorrhage (CBH) on the microstructure of the cerebellar-cerebral circuit is largely unexplored. Objectives: To investigate the effect of CBH on the microstructure of cerebellar-cerebral connections in preterm infants aged <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Furthermore, in agreement with microstructural diffusion tensor imaging research that demonstrated the association between isolated preterm CbH and widespread bilateral cerebello-cerebral circuit alterations 48 , we showed that isolated preterm CbH is linked to widespread cortical gray matter alteration patterns that include bidirectional changes in cortical thickness and cortical surface area. There are several, not mutually exclusive, explanations for the exposed patterns 49,50 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, in agreement with microstructural diffusion tensor imaging research that demonstrated the association between isolated preterm CbH and widespread bilateral cerebello-cerebral circuit alterations 48 , we showed that isolated preterm CbH is linked to widespread cortical gray matter alteration patterns that include bidirectional changes in cortical thickness and cortical surface area. There are several, not mutually exclusive, explanations for the exposed patterns 49,50 .…”
Section: Discussionsupporting
confidence: 89%
“…For instance, homologous regions of the ipsilateral hemisphere might be included in a broader neuronal network that indirectly, for instance via the corpus callosum, suffers from the functional disconnection of the cerebellum 46 . This hypothesis lends support from studies that suggest that the injury is not confined to the site where it initially occurred and that it may result in experience-dependent structural remodeling of the entire cerebello-cerebral circuit 48,52,64 . In line with this view, the differences found between case-cohort groups might as well reflect data that are consistent with the more contemporary network-based view of the neural correlates for cognitive dysfunction.…”
Section: Cortical Cluster Cbh#3 Cg#3mentioning
confidence: 53%
“…Region of interest for the pons was chosen at the level of the middle cerebellar peduncles with a central circle of 2 mm 2 area. Regions were manually positioned on the FA map and copied to the ADC map as described in a previous study [15].…”
Section: Methodsmentioning
confidence: 99%
“…FA and ADC values were measured bilaterally in the centrum semiovale, in the posterior limb of the internal capsule, and in the genu and splenium of the corpus callosum [10]. Regions were manually positioned on the FA map and copied to the ADC map [11]. To validate our data, 20 infants selected at random were analyzed by two independent observers.…”
Section: Methodsmentioning
confidence: 99%